The Impact of Accounting Conservatism in Mediating Auditor Rotation and Audit Quality - Zul Kahfi; Andi Nurhasanah; Idayanti Nursyamsi (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2025)
The research data were gathered from Public Accounting Firms (KAP) in Makassar City that consented to participate. A field research methodology was employed, with primary data collected through questionnaires distributed to 34 respondents. The data were then analyzed using Structural Equation Modeling (SEM) with Smart PLS software. The results indicate that auditor rotation has a positive and statistically significant effect on accounting conservatism. Additionally, the findings reveal that auditor rotation also significantly enhances audit quality, with accounting conservatism acting as a mediator in this relationship. This suggests that accounting conservatism plays a crucial role in strengthening the impact of auditor rotation on audit quality, providing valuable insights for both academic research and practical applications in the auditing profession.